Development of Multi Seeds Oil Expeller - Olaoye, I. O.; Salako, Y. A.; Owolarafe, O. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Multi seeds oil expeller was designed fabricated and evaluated using screw press principle. It was designed and fabricated based on the data obtained on the properties of the oilseeds. The performance of the machine was carried out using a 3 x 3 x 3 factorial experimental design with the following type of seeds (palm kernel, soya bean and groundnut seed), worm shaft speed of 47.6, 87and 92 rpm, and moisture content of 5, 10, and 15 %  w.b as factors. Data collected include oil yield, volumetric flow rate of oil, throughput capacity and efficiency of the machine. The results showed that increase in moisture content as stated has direct effect on oil yield and efficiency of the expeller, but has an inverse effect on volumetric flow rate for the three oil seeds. Increase in worm shaft speed as stated increased oil recovery for palm kernel from 19.1 to 23.0%, soya beans from 0.0 to 16.0% and groundnut from 7.3 to 31.7%. Increase in worm shaft speed as stated increased the oil yield, throughput capacity as well as the efficiency of the machine for all the oil seeds. The efficiency increased from 39.4 to 52.1%; 0.0 to 82.1% and 53.1 to 72.0% for palm kernel; soya bean and groundnut, respectively. These results were found to be significant (p<0.05) when tested using one way analysis of variance (ANOVA) and Duncan’s multiple range test.  The study concluded that, the developed multi-seed expeller performed well within the conditions of operation and could have a potential for improving the production of vegetable oil if adopted by small and medium scale processors.